Using phenolic compounds from the Mediterranean Sea west of Egypt to categorize the sediment quality - Maha Ahmed Mohamed Abdallah; Ahmed E. Alprol (Discover Materials)
Abstract Background and aim Despite having a low population, Egypt’s west coast is heavily industrialized resulting in large amounts of industrial wastewater that are dumped directly into the sea, severely polluting the area with various toxins. Numerous human activities release phenolic chemicals into the environment, which can be found in water and sediment. These materials are used to make compounds such as dyes, pesticides, explosives, and pharmaceuticals in a variety of industrial processes. Insufficient research has been done on the infiltration of phenolic compounds, which are organic serious pollutants, into the aquatic environment along the Mediterranean coast of Egypt, particularly the western shore. The research investigates the ecological dangers and concentration of eleven phenolic compounds found in bottom sediments on Egypt’s coastal area west of Alexandria. Methods Before analysis, stainless steel sieves were used in a mechanical sieving system to homogenize and size-fractionate samples of superficial sediment that were gathered from each of the 15 measurement locations along Egypt’s west coast. Total nitrogen and total organic carbon were also determined. Samples of dried bottom sediment were extracted with a solution of NaOH and methanol in order to determine the phenolic compounds, the final concentrated extract volume of each sample was reduced to 1.0 ml under a mild stream of purified nitrogen gas. A high performance liquid chromatograph (HPLC) (Series 1100, Agilent Technology Inc., Santa Clara, CA, USA) fitted with an autosampler, vacuum degasser, quaternary pump, and diode array detector was used to analyze eleven phenolic compounds. Results The mean concentration of total eleven phenolic ranged between 1.02–5.62 µg g−1 with the mean value of 3.17 µg g−1 (SD, ±1.68), respectively. It was discovered that the concentration of additional phenolic compounds was not uniform, with their share of less than 10% in the total phenolic compounds. Conclusion Phenol was the most prevalent compound, with pentachlorophenol (PCP) coming in second with a normal centralization of 18.454 and 10.785 µg g−1, respectively. It was found that the remaining phenolic compounds had heterogeneous convergences, with less than 10% of them contributing to the total amount of phenolic compounds. Due to several activities, including force stations that utilize tar instead of gas, the oil pipe organization, and several tourist towns, the SidiKirir and Dabaa zones had the highest quantities of phenol and pentachlorophenol.